TIME DEPENDENT EFFECT OF PLANT EXTRACT GLYVIMA ALONE AND IN COMBINATION WITH INSULIN ON THE LIPID PROFILE IN ALLOXAN DIABETIC RATS - DIANA, C.M.; NAMPOOTHIRI, V.K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2006)
Administration of a plant extract, glyvima was found to decrease the serum glucose and cholesterol concentrations in alloxan induced male albino rats. In combination with insulin glyvima was found to be more effective. The present paper deals with time-dependent activity of gly vima and insulin (15.30 and 45 days) on the lipid profile. Animals were observed for physiological responses, mortality, food and water intake and body weight changes.